Resposta :
[tex]\begin{cases} 9 {}^{2x} \: . \: 3 {}^{y} = 1 \\ 3 {}^{x - y} = 81 \end{cases} \\ [/tex]
[tex]\begin{cases} 3 {}^{4x} \: . \: 3 {}^{y} = 1 \\ 3 {}^{x - y} =3 {}^{4} \end{cases} \\ [/tex]
[tex]\begin{cases} 3 {}^{4x + y} = 1 \\ x - y =4 \end{cases} \\ [/tex]
[tex]\begin{cases} 3 {}^{4x + y} = 3 {}^{0} \\ x - y =4 \end{cases} \\ [/tex]
[tex]\begin{cases} 4x + y = 0 ⟶y = - 4x \\ x - y =4 \end{cases} \\ [/tex]
[tex]x - ( - 4x) = 4 \\[/tex]
[tex]x + 4x = 4 \\ [/tex]
[tex]5x = 4 \\ [/tex]
[tex]\boxed{x = \frac{4}{5} } \\ [/tex]
[tex]y = - 4 \: . \: \frac{4}{5} \\ [/tex]
[tex]\boxed{y = - \frac{16}{5} } \\ [/tex]
[tex]\boxed{(x \: , \: y) = ( \frac{4}{5} \: ,\: - \frac{16}{5} ) } \\ [/tex]
att. yrz